2015
DOI: 10.1007/s11894-015-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Biologic Agents in Ulcerative Colitis and Crohn’s Disease

Abstract: The goals of therapy in inflammatory bowel disease (IBD) are the induction and maintenance of clinical and biological remission. Mucosal healing is desirable to prevent complications and reduce the need for surgery, hospitalizations, and steroid exposure. Therapeutic monoclonal antibodies (biologic agents) have revolutionized the treatment of IBD. The initial magnitude of the clinical/biologic response to these agents has been associated with a number of underlying phenotypic features in the recipient. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
0
14
1
2
Order By: Relevance
“…While the subsequent Tailored Treatment With Infliximab for Active Luminal Crohn's Disease (TAILORIX) study found no additional benefit of proactive TDM‐guided dose intensification after induction therapy compared with usual care for the combined primary endpoint of steroid‐free clinical and endoscopic remission . However, a retrospective observational study found significantly lower rates of discontinuing infliximab in IBD patients who had proactive TDM compared to those who had reactive TDM (10% vs 31%, P = .009) . There was, however, potential for confounders in this study.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…While the subsequent Tailored Treatment With Infliximab for Active Luminal Crohn's Disease (TAILORIX) study found no additional benefit of proactive TDM‐guided dose intensification after induction therapy compared with usual care for the combined primary endpoint of steroid‐free clinical and endoscopic remission . However, a retrospective observational study found significantly lower rates of discontinuing infliximab in IBD patients who had proactive TDM compared to those who had reactive TDM (10% vs 31%, P = .009) . There was, however, potential for confounders in this study.…”
Section: Resultscontrasting
confidence: 62%
“…Data on benefits of proactive TDM over empiric dosing or reactive TDM are mixed, making recommending a regular interval for repeating TDM among patients who maintain response difficult . The TAXIT study compared TDM‐guided dosing to maintain infliximab levels within a therapeutic range, to dosing based on clinical symptoms and CRP, among infliximab responders following an initial dose optimisation phase .…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of optimising the IFX therapy in IBD and other inflammatory diseases’ treatment are amply acknowledged in the literature. In fact, adjusting the IFX doses (either escalating or de‐escalating) and the infusion intervals has been proved to be a clinically powerful tool and a cost‐effective strategy . For those reasons, a serious effort of the medical and research community has been recently applied to the development of novel point‐of‐care assays concerning the IBD patients monitoring .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the underlying reasons for this variability, monitoring of serum IFX concentrations and of the formation of anti‐drug antibodies during therapy (Therapeutic Drug Monitoring, TDM) is a powerful tool to aid physicians in the therapeutic decision‐making process in the case of loss or of suboptimal response . Moreover, TDM may also support IFX de‐escalation in case of supratherapeutic serum concentrations, enhancing the cost‐effectiveness of the therapeutic process and avoiding unnecessary side effects …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, monoclonal antibodies have been developed to block cytokine pathways implicated in chronic inflammation. For instance, blockade of the Th1 and Th17 cell pathways by targeting the shared anti-p40 subunit of IL-12/IL-23 with the monoclonal antibody Ustekinumab is rapidly advancing through clinical trials as a novel treatment for moderate-to-severe CD (101, 102). ILCs have also received increasing attention as novel targets for the treatment of inflammatory diseases given some of their analogous signaling pathways with T cells (103).…”
Section: : Manipulation Of Intestinal Microbiota and Host-microbiotamentioning
confidence: 99%